2014
DOI: 10.3390/ijerph110909822
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Prolactin against Methylmercury-Induced Mutagenicity and Cytotoxicity on Human Lymphocytes

Abstract: Mercury exhibits cytotoxic and mutagenic properties as a result of its effect on tubulin. This toxicity mechanism is related to the production of free radicals that can cause DNA damage. Methylmercury (MeHg) is one of the most toxic of the mercury compounds. It accumulates in the aquatic food chain, eventually reaching the human diet. Several studies have demonstrated that prolactin (PRL) may be differently affected by inorganic and organic mercury based on interference with various neurotransmitters involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
1
9
0
4
Order By: Relevance
“…In our study, Hg treatment showed a significant enhancement in CAs. Silva- Pereira et al (2014) reported increases in CAs after Hg compound exposures to blood cells and HL-60 cells (an acute myeloid leukemia lineage). In corroboration of our data, increased cytogenetic damage and genotoxicity was observed in blood cultures (Bahia et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, Hg treatment showed a significant enhancement in CAs. Silva- Pereira et al (2014) reported increases in CAs after Hg compound exposures to blood cells and HL-60 cells (an acute myeloid leukemia lineage). In corroboration of our data, increased cytogenetic damage and genotoxicity was observed in blood cultures (Bahia et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Although the pituitary gland has already been highlighted as a potential target of mercury accumulation ( 4 ), the effects of this metal on the regulation of hormonal release are unclear. Previous studies showed associations (both positive and negative) between serum PRL and mercury exposure ( 6 ). This dual effect may be explained by different interactions between mercury species (inorganic and organic) and PRL secretion by the pituitary gland, which is controlled by neurotransmitters such as dopamine.…”
Section: Introductionmentioning
confidence: 90%
“…3 Another important mechanism of mercury genotoxicity is its ability to produce free radicals that can cause DNA damage. 4 Based on previous research on thimerosal and its importance in vaccines, this study aimed to examine the potential cytotoxic and genotoxic effects of specific thimerosal concentrations on human peripheral blood lymphocyte culture. 5…”
Section: Introductionmentioning
confidence: 99%